Typification of some taxa of the North and Center of the Iberian Peninsula described by J.M.C. Lange - Silva Pando, Francisco Javier; Pino Pérez, Rubén (Botanica Complutensis, 2019)
The herbarium of Lange conserved in C is important for the study of the flora of the Iberian Peninsula, mainly by the numerous new names described for the territory, based on materials collected by Lange himself in his trips to the Iberian Peninsula or from other authors. Many of these names have already been treated and we now continue the processes of typing other new names, based on the materials that are preserved in C. Lectotypes are designated for seven taxa (Rumex biformis Lange, Arenaria incrassata Lange, Cakile monosperma Lange, Sedum anglicum var. raji Lange, Ulex micranthus Lange, Antirrhinum ambiguum Lange, and Trisetum hispidum Lange) from seven families described by J.M.C. Lange from the Iberian Peninsula. We also discuss taxonomic status of these names, when names are now treated as synonyms, the currently accepted name is given.